Optimización de la función de transferencia de emisión en transductores de terapia diseñados con piezocompuestos de estructura 2-2 mediante ajuste de la fracción volumétrica - Rodríguez Rúa, Orlando R.; Chong-Quero, J. Enrique; Leija, L.; Vera, A.; Otero, J. Antonio; Rodríguez-Ramos, Reinaldo; Bravo-Castillero, Julián (Revista Mexicana de Ingenieria Biomedica, 2006)
The design of ultrasound transducer for therapy applications is generally made with the purpose of maximizing its response to the electric stimulation. However, the drifts introduced by the dispersion and the temperature effects in the parameters of the elements that conform the generating system of ultrasonic waves, should be considered. With this purpose different approaches have been suggested in the literature. Among them is the use of piezocomposite materials of low losses for the fabrication of the transducer. In this way it is possible to increase the bandwidth of the transmission transfer function (TTF) of the transducer, resulting in a wider tolerance to the mentioned drifts. Additionally, a more uniform ultrasound radiation field is achieved which is fundamental in many therapy applications. This work presents a new approach for the optimization of the TTF of therapy transducers, where the active material is a piezocomposite of 2-2 structure. The study considers the homogenized characteristics of the transducer in function of its volumetric fraction and the interrelation of these parameters with the electric stimulation output stage by means of its internal impedance Rg. The obtained results suggest a relationship inversely proportional of the optimal volumetric fraction of the piezocomposite and the impedance Rg, for a maximum of the TTF.